Improving mass change estimation in Panama with the GRACE/GFO gravity field using the variational mode decomposition - Jian, Guangyu; Xu, Chuang; Yao, Chaolong (Frontiers in Earth Science, 2023)
In this study, we aim to estimate the mass changes in Panama using the Gravity Recovery and Climate Experiment level-2 products, which are formed as spherical harmonic coefficients (SHCs) and limited by stripe noise. The empirical de-striping method and the temporal filter achieved by empirical mode decomposition can be used to reveal the signals but are still limited in signal reservation and noise reduction. Toward this end, we put forward a novel efficient strategy that uses the variational mode decomposition algorithm to filter the time series of each SHC separately. Based on the two reliable mascon products and in-situ short-term groundwater observations, various comparisons in spatial, spectral, and temporal domains are implemented. In addition, the SNR (signal-to-noise ratio) index and the three-cornered hat method are adopted for assessment. The main results and conclusions are as follows: 1) Our filter outperforms the two previous methods with the best SNR (2.14) and the lowest Panama regional uncertainty (70 mm) for all available months. 2) Our estimate of the basin groundwater storage is closest to one of the groundwater observations with the maximum correlation coefficient (0.72, p<0.05). This result suggests that our method seems to detect small-scale mass signals that are undetectable in the two mascon products. Our work can provide for studying the mass change of small-scale basins in the low latitudes.